Adolescents' perceptions about smokers in Karnataka, India - N Devadasan; Elias Maya A; Bhojani Upendra M (BMC, 2011)
Abstract Background Prevalence of tobacco use among adolescents in India is very high. Despite many epidemiological studies exploring tobacco use among youth, there is no published data on adolescents' perceptions about smokers in Indian society and its implications on tobacco control. Methods A cross-sectional study was conducted using a stratified random sampling with probability proportional to school-type (government or private owned). Data was collected using a pretested, self-administered, anonymous questionnaire with a mix of close and open-ended questions from a sample of 1087 students. Chi-square test was used to measure associations. Qualitative data was analysed through inductive coding. Results The response rate for the study was 82.5% and the sample population had a mean age of 16.9 years (SD = 1.9) with 57.8% male students. Majority of respondents (84.6%) reported negative perceptions about smokers while 20.4% of respondents reported positive perceptions. Female students reported significantly higher disapproval rate (negative perceptions) for smoking compared to male students (89.7% Vs 71.6% in case of male smoker; 81.2% Vs 67.3% in case of female smoker). Dominant themes defining perceptions about smokers included 'hatred/hostility/Intolerance', 'against family values/norms', 'not aware of tobacco harms' and 'under stress/emotional trauma'. Themes like 'culture', 'character' and 'power' specifically described negative social image of female smoker but projected a neutral or sometimes even a positive image of male smoker. There was a significant association between adolescents' positive perceptions of smokers and tobacco use by themselves as well as their close associates. Conclusions Adolescents' stereotypes of smokers, especially female smokers are largely negative. We suggest that tobacco control interventions targeting adolescents should be gender specific, should also involve their peers, family and school personnel, and should go beyond providing knowledge on harmful effects of smoking to interventions that influence adolescents' social construct of smoking/smoker.